Gang talk and strategic moralisations in Danish drug policy discourses on young and recreational drug users - Søgaard, Thomas Friis (Retreat or entrenchment?, 2021)
In Denmark, a moralization of recreational use of drugs has lately occurred. The use is interpreted in a neo-liberal framing seeing the user who can chose as selfish, not regarding the negative consequences of drug use in a wider sense, and the legislation has been sharpened.